Effectiveness of local application of antiseptic with octenidin dihydrochloride molecule in smoking women with ASC-US and LSIL - O.O. Akulina (Publishing House TRILIST, 2021)
This article presents the results of our own experience of topical use of the Prodexin antiseptic that is contained an octenidine dihydrochloride molecule as a monotherapy for ASC-US and LSIL cervical pathology (identified with in fluid cytology) associated with human papillomavirus in smoking women. Study objective: To study the efficacy of topical application of the octenidine dihydrochloride molecule in the Prodexin vaginal suppositories in the treatment of smoking women with ASC-US and LSIL. Materials and methods. The study involved 45 female smokers with identified ASC-US or LSIL. The complex of examination included: Pap test based on liquid cytology, testing for human papillomavirus 16, 18, 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, 68 types in a quantitative format, screening for the causes of vaginitis, extended colposcopy to exclude cervical intraepithelial neoplasia II+. Prodexin suppositories were used according to a 3-month treatment regimen (20 suppositories daily, and then 10 suppositories in two consecutive cycles). Results. Clinical and laboratory assessment of the therapy effectiveness has convincingly shown its positive effect on the vagina and cervix. Treatment with the Prodexin antiseptic associated with microbiota normalization, colposcopic picture improvement and changes in the Pap smear to NILM I or II. Regress to NILM was recorded in 20 (86.9%) patients with ASC-US and in 15 (68.8%) women with LSIL. Conclusions. Prodexin allows to avoid a worsening of the situation and prevent the changes progression in HSIL. Proposed treatment had no side effects, was convenient to use and did not require additional visits to doctor during therapy. The control over the human papillomavirus and study of the viral load has been postponed for 6-12 months from the beginning of the examination, that will be the second stage of work.